Implementation of Monetary Policy in Ems Countries Participating in the Exchange Rate Mechanism - Galy, Michel (Washington, D.C. : International Monetary Fund, 1992)
This paper investigates the issue of monetary interdependence among members of the European Monetary System over the period 1979-91 and the leadership role attributed to the German central bank in the process of monetary integration, and looks for possible changes in central banks' behaviors. Econometric evidence supports somewhat the German leadership role but suggests also the development of an increased interdependence between French and German monetary policies after 1981-82; meanwhile, the Italian and more recently the Spanish central banks appear to have preserved a more significant measure of monetary autonomy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet